Implementation of Community Diagnosis in Suppressing New TB Cases in Village X - Gita Manerlin Kasihita Simatupang; Clement Drew (Journal La Medihealtico, 2026)
The purpose of this study was to increase public knowledge in Kiarapayung Village, within the Pakuhaji Community Health Center (Puskesmas) working area regarding pulmonary TB and its prevention. Community diagnosis in the Pakuhaji Community Health Center working area used the Blum Paradigm, with data from mini-surveys, interviews, and observations. Problem priorities were determined through USG (Urgency, Seriousness, Growth), non-scoring Delphi, and Fishbone and Five Whys analysis for root causes. Interventions included pulmonary TB education, coughing/sneezing etiquette practices, and proper handwashing. Monitoring was conducted using the PDCA cycle, while evaluation used a systems approach. Based on the Blum Paradigm, lifestyle factors play a role in the high number of TB cases. The intervention results showed that 24 participants (60%) obtained a post-test score of ≥70 points, and there was an increase in the average pre-test and post-test scores of 46.6%. One random participant was able to demonstrate coughing etiquette and proper handwashing.